Identification of enterobacteria in viscera of pigs afflicted with porcine reproductive and respiratory syndrome and other viral co-infections. (October 2020) - Zhao, Ge; Zhang, Lujie; Li, Charles; Zhao, Jianmei; Liu, Na; Li, Yuehua; Wang, Junwei; Liu, Liheng
Abstract: In order to investigate enterobacteria presence involved in the secondary infections in Porcine Reproductive and Respiratory Syndrome (PRRS) pigs with different viral co-infections, we identified enterobacteria for guiding clinical treatment. Twenty-one diseased pigs were diagnosed with the PRRS virus (PRRSV) and other 7 virus primers by PCR/RT-PCR in the lung and spleen samples. Enterobacteria were isolated using MacConkey agar from 5 visceral samples of PRRS pigs, and identified by 16S rDNA sequencing. PRRSV was positive in 100% of the lung samples and 81.0% of the spleen samples. Seven diseased pigs were diagnosed with only PRRSV infection (33.3%), 7 pigs with PRRSV and 1 or 2 other viruses (33.3%) and 7 pigs with PRRSV and more than 2 types of other viruses (33.3%). PRRSV was more inclined to co-infect pigs with porcine group A rotavirus (PARV) with the co-infection rate of 52.4% (11/21). Approximately 13 types of bacteria were successfully isolated from lung, spleen, liver, kidney and lymph node samples of different PRRS pigs. Enterobacteria were isolated in 100% of lung, liver and lymph samples from pigs infected with PRRSV alone. However, the isolation rates were significantly decreased in the more than 3 viruses co-infection group. Escherichia coli was the most prevalent bacterium, followed by Morganella, Proteus, Shigella, Salmonella, Klebsiella and Aeromonas . Most of the isolated enterobacteria were opportunistic pathogens. Therefore, timely combination with antimicrobial agents is necessary for effective treatment of PRRS-infected pigs. Highlights: PRRSV was more inclined to co-infect with PARV. Pigs co-infected with more virus, less enterobacteria were isolated from their viscera. Enterobacteria isolated from viscera of PRRS pigs were opportunistic pathogens. coli, Morganella and Proteus were the most prevalent enterobacteria. Secondary infection of enterobacteria should be considered in PRRS treatment.